Power electronic converters and systems frontiers and applications - Trzynadlowski, Andrzej M. (London, United Kingdom The Institution of Engineering and Technology, 2015)
The book is written at postgraduate level and comprises N chapters dealing with the following subjects: semiconductor power devices; multilevel converters; multi-input converters; modular converters; matrix converters; soft-switching converters; Z-source converters; switching power supplies; smart power electronic modules; permanent magnet synchronous motor drives; induction motor drives; wind energy systems; photovoltaic energy systems; automotive energy systems; shipboard power systems; power grid; distribution generation; microgrids; uninterruptible power supplies; wireless power transfer; and power electronics system control.
Electronic reproduction.
Keywords: Power electronics; Electric current converters; Distributed generation of electric power; Electric power transmission; Photovoltaic power systems; Power semiconductors; Uninterruptible power supply; Wind power plants; Electronic books